The genetics of urinary microbiome, an exploration of the trigger in calcium oxalate stone - Yang, Yuanyuan; Miao, Lintao; Lu, Yuchao; Wang, Shaogang (Frontiers in Genetics, 2023)
Background: Kidney stone disease is a global disease; however, it has not been totally understood.Calcium oxalate (CaOx) stone is the dominant type of kidney stone, and the potential factors involved in its formation are yet to be explored. Clinically, we found that the CaOx stones in patients were mainly unilateral; therefore, systemic factors cannot explain them, although some local factors must be involved. Urinary microbiota is involved in stone formation. Therefore, this study aimed to explore the association between the urinary microbiota and CaOx stones and provide insight into the medical treatment and prevention of CaOx stones.Methods: Sixteen pelvic urine samples were collected from the stone and non-stone sides of patients with unilateral CaOx stones following strict criteria. The 16S rRNA gene sequencing was performed on each pair of pelvic urine samples at the species level. Many bioinformatic analyses were conducted to explore the potential factors affecting CaOx stone formation.Results: Although no statistically significant difference was found between the overall microbiota of the pelvis urine from the two sides. Many biologically distinct taxa were observed, including many bacteria found in previous studies, like Proteobacteria, Actinobacteria, Firmicute and Enterobacter cloacae and so on. What's more, despite these common bacteria, our current study added to these bacterial communities with additional identification of Deinococcus-Thermus, Coriobacteriia , Porphyromonas and Ralstonia. To predict the functions of these microbiota, Kyoto Encyclopedia for Genes and Genomes and MetaCyc analysis were conducted and immunometabolism might be an important pathway. Moreover, a random forest predictor was constructed to distinguish the stone side from the non-stone side, with an accuracy of 62.5%.Conclusion: Our research profiled the microbiome in the pelvis urine from both the stone and nonstone sides of patients with unilateral CaOx stones, provided insight into the dominant role of urinary dysbiosis in CaOx stones formation. Furthermore, this study also predicted the potential crosstalk among urinary microbiota, immunometabolism, and CaOx stones.